(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Type 2 Diabetes Mellitus is a chronic disease that has a high prevalence in Pakistan, making it one of the major public health problem. Among all patient reported health outcomes in diabetic population, Health Related Quality of Life (HRQOL) is an important parameter to be considered for improvement. Objective: The objective of this study was to determine the pattern of relationship between personal-background characteristics and dimensions of health-related quality of life (HRQOL) in diabetic patients. Methodology: It was a cross sectional descriptive study including 385 Type 2 DM patients, aged 18 - 60 from different diabetic centers of Lahore. Data was collected by a validated data collection form (questionnaire), consisting of three parts; including (1) Socio-demographic and medical (diabetes related) personal-background characteristics, (2) General health-related QOL, and (3) Diabetes specific instrument. Data were analyzed with descriptive statistics, correlation and multi-stage stepwise regression utilizing SPSS. Results: This study involved 385 diabetic patients including 204 females (52.9%) and 181 males (47%). In this sample, 43.8% of the patients were in the age group of 51—60 years. The mean age of participants was 48.7 years. The majority of participants were females (52.9%), 85.4% of participants were married, 83.1% lived in the city, 60.2% were employed, and 50.6% of patients were the family breadwinner. Over half of the participants (49.6%) had college education. As to medical characteristics, 60.2% had a family history of diabetes, 15.5% had health insurance, and 53.2% had diabetic complications. Conclusion: Diabetic patients face great challenges in many dimensions of HRQOL, significantly influenced by their demographic characteristics, employment status, past medical history, everyday life, pain, sleep, extent of treatment satisfaction, and psychological concerns. Overall, the HRQoL score was relatively low in females than in males, indicating the importance of improvement in health care interventions to ensure better quality of life and improved health outcomes.